Urban‐induced modifications to the diurnal cycle of rainfall over a tropical city. (21st January 2021) - Doan, Quang‐Van; Dipankar, Anurag; Simón‐Moral, Andrés; Sanchez, Claudio; Prasanna, Venkatraman; Roth, Matthias; Huang, Xiang‐Yu
Abstract: There is still no consensus on the mechanisms that modify precipitation over and around cities, especially for those located in the tropics where convective processes primarily drive rainfall. Here we contribute to the ongoing discussion about the urban‐associated precipitation by investigating the urban effect on the diurnal cycle of rainfall over Singapore. We use the urban version of the numerical weather prediction system of the Meteorological Service Singapore (hereafter called uSINGV) at a 300 m horizontal resolution to simulate the rainfall conditions over Singapore and its surroundings during the inter‐monsoon period between 2010 and 2014. Two simulations with different land surface conditions are conducted: one with urban areas (i.e. present conditions) and one without urban areas. uSINGV is shown to perform well for rainfall when compared to observations. Comparison between simulations reveals that the urban area is responsible for the formation of a rainfall "hot spot" over Singapore and Johor Bahru, located at the southern tip of the Malay Peninsula, and the urban effect is accountable for 20–30% of total rainfall during late afternoons and evenings, highlighting a strong urban effect on localized rainfall over a tropical city. Enhancement of convection due to the urban heat island effect, increased frictional convergence due to buildings' drag, the seaward shift of the sea‐breeze front, and the increased inflow of boundary‐layer moisture by the stronger sea breeze are suggested as most probable reasons for the increased rainfall in the urban area. Abstract : Diurnal cycle of simulated rain rate from URB and NO_URB. The values shown here are five‐November (2010–2014) averages over the rectangle shown in the inset map which includes parts of Singapore and Johor Bahru in Malaysia (referred to as SGJB in the text). The colour‐shaded areas indicate the uncertainty ranges, which are derived using a bootstrapping approach and defined as a range between 25 and 75% quantiles of the bootstrap means